2004
DOI: 10.13001/1081-3810.1122
|View full text |Cite
|
Sign up to set email alerts
|

Two characterizations of inverse-positive matrices: the Hawkins-Simon condition and the Le Chatelier-Braun principle

Abstract: It is shown that (a weak version of) the Hawkins-Simon condition is satisfied by any real square matrix which is inverse-positive after a suitable permutation of columns or rows. One more characterization of inverse-positive matrices is given concerning the Le Chatelier-Braun principle. The proofs are all simple and elementary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 10 publications
0
43
0
1
Order By: Relevance
“…An inversepositive matrix A is a square invertible matrix that satisfies the above condition that all elements of the inverse are nonnegative. Intuitively, inverse-positive matrices play an important role in many real-world systems (Fujimoto and Ranade 2004), as production volumes in an economic system and chemical concentrations in a chemical system are necessarily non-negative. So let us consider the case of LCA.…”
Section: Discussionmentioning
confidence: 99%
“…An inversepositive matrix A is a square invertible matrix that satisfies the above condition that all elements of the inverse are nonnegative. Intuitively, inverse-positive matrices play an important role in many real-world systems (Fujimoto and Ranade 2004), as production volumes in an economic system and chemical concentrations in a chemical system are necessarily non-negative. So let us consider the case of LCA.…”
Section: Discussionmentioning
confidence: 99%
“…The main properties of our technique are consequences of the theory of M-matrices [Fujimoto and Ranade 2004], which are nonsingular, square matrices with the property that their inverses have only positive entries.…”
Section: Total Positivity Conjecturementioning
confidence: 99%
“…The black circle represents the known approximation to the exact solutions at the time t k , and the crosses denote the unknown, new approximations at the time t k+1 . serves the boundedness and the positivity of the solutions of (1), and it makes use of the nonsingularity properties of M-matrices [Fujimoto and Ranade 2004]. Proposition 1.…”
Section: Total Positivity Conjecturementioning
confidence: 99%
“…This section and the next are devoted to the study of a class of matrices introduced by Fujimoto and Ranade [6]. 2).…”
Section: Whs After Reordering Of Columnsmentioning
confidence: 99%
“…With no assumption on the signs of the off-diagonal coefficients, three characterizations of the WHS property are given (section 3). Fujimoto and Ranade [6] have recently considered matrices which are of the WHS type after a suitable reordering of columns (these matrices are said to be of the FR type) and shown that an inverse-semipositive matrix has this property. This result is generalized and we show that, since the FR family of matrices is invariant by a group of transforms, the identification of the FR matrices should take into account the associated group (section 4).…”
Section: Introductionmentioning
confidence: 99%